Boundaries and Spheres of Influence in Domestic Politics and International Relations - Bednarska, Wiktoria (Boundaries and Spheres of Influence in Domestic Politics and International Relations, 2023)
For several decades, the Republic of Korea has been devoting significant attention to the potential of soft power in international relations. The so-called "Korean Wave" has brought numerous benefits to South Korea, including an increased interest in learning the Korean language. This chapter focuses on the growing popularity of South Korean films, TV series, and music, and the impact of this phenomenon on the interest in learning the Korean language among Polish people. The analysis covers the period after the first decade of the 21st century, as it was during this time that the "hallyu" achieved global recognition. Through a review of the literature, conducted surveys, and university enrollment data, this chapter seeks to answer questions regarding how South Korean popular culture is utilized by the Republic of Korea to promote its language and what effects these efforts have had in Poland. The skillful utilization of popular culture potential by South Koreans has allowed them to witness a growing interest in learning the Korean language worldwide, including Poland.